The Impact of Trade Balance of Agri-Food Products on the State’s Ability to Withstand the Crisis - Dragan Dokić; Mirna Gavran; Maja Gregić; Vesna Gantner (HighTech and Innovation Journal, 2020)
The crisis represents a disorder that in contemporary society increasingly occurs. Crises are often the result of some earlier solutions. The situation in agricultural production in Croatia has been negative for years. Inadequate tax and high administrative burdens act to discourage the production process and impede the competitiveness of farmers. Furthermore, the measures taken to create added value are not enough, they can even be said to be wrong. The current crisis Covide-19 caused a disturbance on the market in terms of trends of supply and demand. The crisis period will show whether the country has an adequate strategy to overcome all the economic problems ahead. The aim of this paper was to analyze the readiness of the Republic of Croatia for crisis periods in terms of food security by analyzing the volume of agricultural production, the balance of foreign trade of agri-food products as well as the structure of total agri-food product trade. The determined trend of increasing deficits in agri-food products in foreign trade balance, particularly with EU countries implies the state's unenviable position regarding the food security indicating the need for implementation of adequate measures in the direction of the market organization and to facilitate investment in sustainable agriculture production systems.